2016
DOI: 10.15835/nbha.44.1.10224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc and Bio Fertilizers on Antioxidant Enzymes Activity, Chlorophyll Content, Soluble Sugars and Proline in Triticale Under Salinity Condition

Abstract: In order to study the effects of bio fertilizers and zinc fertilizer on antioxidant enzymes activity, chlorophyll content, soluble sugars and proline in triticale under salinity condition, a factorial experiment was conducted based on randomized complete block design with three replications under greenhouse condition. Experiment factors were included salinity in four levels [no-salt (control or S 0 ), salinity 20 (S 1 ), 40 (S 2 ) and 60 (S 3 ) mM NaCl) equivalent of 1.85, 3.7 and 5.55 dS m −1 respectively], f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Under high salinity stress, the application of nano Zn to the soil enhanced crop productivity in Triticale by 39% compared with the control set without nano Zn addition [100]. Significant improvement in fresh weight and dry weight in rice [101], production of biomass in sunflower [102], and crop yield in wheat [92] have been reported under salt stress as a result of the application of nano Zn at the rates of 25 or 50 mgl −1 .…”
Section: Role Of Zn and Se In Plants Under Salinity Stressmentioning
confidence: 99%
“…Under high salinity stress, the application of nano Zn to the soil enhanced crop productivity in Triticale by 39% compared with the control set without nano Zn addition [100]. Significant improvement in fresh weight and dry weight in rice [101], production of biomass in sunflower [102], and crop yield in wheat [92] have been reported under salt stress as a result of the application of nano Zn at the rates of 25 or 50 mgl −1 .…”
Section: Role Of Zn and Se In Plants Under Salinity Stressmentioning
confidence: 99%
“…Biochar concentrations increased the antioxidant activities in the wheat plants by improving cell growth, and soil–plant water relationship 67 69 . Nanoparticles increased the POD and APX activity to mitigate the water scarcity situation as reported by 70 – 73 . Correlation analysis showed a linear relationship among treatments and recommended the usage of brassinosteroids for increasing stomatal conductance, leaf area index, relative water contents, and chlorophyll contents and for ameliorating the effect of drought stress.…”
Section: Discussionmentioning
confidence: 85%
“…A study conducted with Chrysanthemum balsamita L. reported that Zn treatments decreased the content of proline compared to the control group, and the lowest content of proline was obtained from 1 g L −1 Zn treatments [59]. In a study that was conducted in Triticale, it was reported that the Zn fertilizers increased the content of proline, but this increase was not at a significant level [60]. Behtash [61] reported that only zinc treatments did not have a significant effect on proline content, but the content of proline decreased by 337% at a dose of 10 mg L −1 Zn.…”
Section: Soluble Protein (Sp) Proline Chlorophyll and Carotenoid Contentmentioning
confidence: 98%